Redistributive innovation policy, inequality, and efficiency. (30th July 2019) - Basu, Parantap; Getachew, Yoseph
Abstract: We examine the efficiency and distributional effects of regressive and progressive public R&D policies that target high‐tech and low‐tech sectors using a heterogenous‐agent growth model with in‐house R&D and incomplete capital markets. We find that such policies have important implications for efficiency and inequality. A regressive public R&D investment financed by income tax could boost growth and welfare via a positive effect on individual savings and effort. It could, however, also lower growth and welfare via its effect on the efficiency–inequality trade‐off. Thus, the relationship between public R&D spending and welfare is hump‐shaped, admitting an optimal degree of regressivity in public R&D spending. Using our baseline model, and the US state‐level GDP data, we derive the degree of regressiveness of public R&D investment in US states. We find that US states are more regressive in their R&D investment than the optimal regressiveness implied by our growth model.